Migrant Integration in Finland:learning-processes of immigrant women - Yeasmin, Nafisa; Kirchner, Stefan (Routledge, 2020)
Understanding women’s integration and strengthening their resilience encompass self-determination, which is one of the main attributes to facilitate the integration of this group of people into the host society. Immigrant women need to build their capacities to navigate their way in the host society, and it is necessary to increase self-determination among immigrant women in order to sustain their well-being and ability to interact with the host society. Otherwise, this can create contextual challenges not only for them, but also for the society to which they belong. The chapter states that the motivation of immigrant women to be integrated into the host society could be increased by empowering them. They need skills and abilities to interact with others and feel a sense of autonomy. Considerable attention is needed to harness the basic psychological needs of immigrant women in order to integrate them successfully into the Arctic society. The chapter aims to answer the question of how integration of immigrant women can be improved, and how learning can empower immigrant women to play a more active role in their integration into Finnish society.